Technical Perspective: Borrowing Big Code to Automate Programming Activities. - Rinard, Martin C. (Communications of the ACM, 2019)
The article presents an introduction to a paper which discusses techniques for leveraging big code to automate programming activities of selecting understandable names for Javascript identifiers and generating type annotations for Javascript variables.